Antibiotic Resistance of Helicobacter pylori Isolated from Patients after Partial Gastrectomy: A Retrospective Study - Lan Li,; Weihua Zhou,; Hongzhang Li,; Chaohui Yu,; Tianlian Yan,; Ningmin Yang,; You-Ming Li, (Turkish Journal of Gastroenterology, 2021)
Background: To determine the prevalence of Helicobacter pylori infection and the antibiotic susceptibility of H. pylori in patients after partial gastrectomy. Methods: Patients who underwent gastroscopy from January 2009 to November 2017 and had a history of partial gastrectomy were retrospectively enrolled in the remnant stomach group. Contemporary non-gastrectomized patients with an endoscopic diagnosis of chronic gastritis were enrolled in the non-operated stomach group. The detection of H. pylori infection was performed by culture and histology. The in vitro antimicrobial susceptibility was examined by the agar dilution method on strains from gastric biopsies. Results: In this study, a total of 728 gastrectomized and 5035 non-gastrectomized patients were included. There was a significantly lower prevalence of H. pylori infection in the gastric-remnant patients (8.65%) than in the non-gastrectomized patients (17.76%) (P < .001) with the diagnostic method of culture. In the gastric-remnant patients, the H. pylori strains had resistance rates to metronidazole, clarithromycin, levofloxacin, amoxicillin, and furazolidone of 100%, 20.63%, 22.22%, 0%, and 0%, respectively. In the nongastrectomized patients, H. pylori resistance to metronidazole, clarithromycin, levofloxacin, amoxicillin, and furazolidone was 90.49%, 24.61%, 21.70%, 0.22%, and 0.11%, respectively. Gastric-remnant patients had a significantly higher metronidazole resistance rate than non-gastrectomized patients (P = .005). Moreover, no significant changes in the resistance to 5 antibiotics were observed among the gastric-remnant patients from different age, gender, and surgical indication groups. Conclusion: Patients after partial gastrectomy showed a lower prevalence of H. pylori infection. Gastric-remnant patients were more likely to harbor metronidazole-resistant H. pylori strains. Cite this article as: Li L, Zhou W, Li H, et al. Antibiotic resistance of Helicobacter pylori isolated from patients after partial gastrectomy: A retrospective study. Turk J Gastroenterol. 2021;32(12):996-1002.